Technology policy and market structure: Evidence from the power sector - Moritz Bohland; Sebastian Schwenen (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
We show how policies to trigger clean technologies change price competition and market structure. We present evidence from electricity markets, where regulators have implemented different policies to subsidize clean energy. Building on a multi-unit auction model, we show that currently applied subsidy designs either foster or attenuate competition. Fixed, price-independent output subsidies decrease firms' mark-ups. In contrast, designs that subsidize clean output via a regulatory premium on the market price lead to higher mark-ups. We confirm this finding empirically using auction data from the Spanish power market. Our empirical results show that the design choice for technology subsidies significantly impacts pricing behavior of firms and policy costs for consumers.
Keywords: D22; D44; D47; 330; Subsidies; Clean Energy; Pricing; Electricity